Development of laminar burning velocity measurement system in premixed flames with hydrogen-content syngas or strong oxidizer conditions in a slot burner. (July 2022) - Li, Yueh-Heng; Liang, Jin-Wei; Lin, Hung-Ju
Abstract: This study presents the experimental determination of laminar burning velocity for critical premixed flames with multiple fuels or strong oxidizers. Experiments were conducted with a slot burner under methane/air, methane/nitrous oxide, and syngas (CH4 /CO/H2 )/air premixed flames conditions with varying equivalence ratios from 0.8 to 1.4. With the flame surface area determined from the Schlieren measurement system and stretch effect corrected by Markstein length, unstretched laminar burning velocity can be garnered according to the conservation of mass. First, the experimental results of methane/air premixed flame velocities were validated by comparing with one-dimensional unstretched burning velocities through numerical simulations with GRI 3.0 mechanism. The experimental results in the equivalence ratio ranging from 0.85 to 1.2 demonstrated errors less than 3.8%. Then, the validated burning velocity measuring techniques were implemented under methane/nitrous oxide and syngas/air premixed flame conditions. Finally, appropriate chemical mechanisms, such as USM or UGM, can be validated for the numerical simulation of critical premixed flames via this proposed laminar burning velocity measuring technique.